Musik Pop dan Kebebasan Berekspresi - Salenussa, Peter Boris (KAMBOTI: Jurnal Sosial dan Humaniora, 2023)
All of artworks always give expression but not all expressions of artworks can be accepted by everyone. Rejection of certain artwork that is considered deviant, it means also resisting the expression of artwork. Music, especially pop music as part of the art often gets a lot of resistance because of the freedom of expression. In some cases denial of artistic expression in pop music in Indonesia, it is done based on norms that are considered to be noble social values.Without intending to assess which is the most correct, this paper will try to trace critically about what is behind the phenomenon of pop music that often reap the denial of freedom of expression. This article is not intended to reconcile the conflict between the many people who have refused the aberrant expression of music with product of pop music itself, but rather tries to lay the base of foundation that can be used by music, especially pop music, in the use of expression responsibly.